Śmierć intelektualistki: Susan Sontag - Kaczmarek, Agnieszka (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2012)
Susan Sontag is the most popular American intellectual. She died after a long and painful illness, i.e. cancer. The goal of this article is to show the relations between Sontag’s fi ction (Death Kit), her real life and intellectual attitudes (Illness as Metaphor, Regarding the Pain of Others). The analysis shows dependencies between Sontag’s writings and her own suffering as well as the experience of death